Anisotropic exciton–polaritons in 2D single-crystalline PEA2PbBr4 perovskites at room temperature. (17th February 2023) - Chu, Zihao; Chen, Huanqing; Mao, Xinrui; Li, Yanping; Xu, Wanjin; Ran, Guangzhao
Abstract: Two-dimensional (2D) single-crystalline perovskites are a suitable material for investigating the strong exciton–photon interaction due to the large exciton binding energy. Here, we grow high-quality 2D single-crystalline PEA2 PbBr4 thin film in situ in between a pair of distributed Bragg reflectors and construct an anisotropic exciton–polariton microcavity. Clear evidence for strong exciton–photon coupling is observed and represented by a large coupling strength of 211.8 meV. The observed transverse electric–transverse magnetic splitting at the point where the in-plane wave vector is zero indicates crystal birefringence. The effective refractive indices for these two orthogonal polarization directions are derived to have a large difference, corresponding to a material index difference of 0.28, and then an in-plane refractive index ellipse is built for the material. This work shows that the 2D anisotropic perovskite microcavity can not only behave as a platform for characterizing the anisotropic properties of a material but also as a promising room-temperature polaritonic device.